Colonized through Art : American Indian Schools and Art Education, 1889-1915 - Lentis, Marinella (Book collections on Project MUSE., 2017)
"An examination of government-controlled schools' use of art education as a process for assimilating American Indian children at the turn of the twentieth century."--Provided by publisher.